2013
DOI: 10.1137/12089243x
|View full text |Cite
|
Sign up to set email alerts
|

Derivation of the Isotropic Diffusion Source Approximation (IDSA) for Supernova Neutrino Transport by Asymptotic Expansions

Abstract: We present Chapman-Enskog and Hilbert expansions applied to the O(v/c) Boltzmann equation for the radiative transfer of neutrinos in core-collapse supernovae. Based on the Legendre expansion of the scattering kernel for the collision integral truncated after the second term, we derive the diffusion limit for the Boltzmann equation by truncation of Chapman-Enskog or Hilbert expansions with reaction and collision scaling. We also give asymptotically sharp results obtained by the use of an additional time scaling… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
24
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(25 citation statements)
references
References 53 publications
1
24
0
Order By: Relevance
“…This would be an alternative to the current version of the IDSA, which still has some mathematical issues that need to be fixed, see [2,3] for more details.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…This would be an alternative to the current version of the IDSA, which still has some mathematical issues that need to be fixed, see [2,3] for more details.…”
Section: Resultsmentioning
confidence: 99%
“…This assumption has been used at least in two different series of papers: the first one is in physics for the approximation of neutrino radiative transfer in core-collapse supernovae [11,2,3], and the second one is in mathematics for the coupling between the kinetic equation and approximations of it (diffusion, Euler, Navier-Stokes...) [8,5,6,7].…”
Section: Motivationmentioning
confidence: 99%
See 1 more Smart Citation
“…The reaction limit is valid in regions where the mean free path κ −1 is negligible compared with the typical length scale of the system. As for the diffusion limit, one can use asymptotic expansion with a different scaling in order to derive this limit, see for example [2]. 6 JÉRÔME MICHAUD with g idsa := h free .…”
mentioning
confidence: 99%
“…In [2], it is shown that this particular coupling mechanism might be problematic and mathematical issues are discussed. The aim of this paper is to study the behavior of the IDSA on a simple radiative transfer model and try to address some of the mathematical issues highlighted in [2].…”
mentioning
confidence: 99%